CLINICAL-IMMUNOGENETIC RELATIONSHIP IN CHILDREN WITH CHRONIC TONSILLITIS AND ASSOCIATED DISEASES - Aminjonovich, Asrorov Akmal (Journal of Medical Genetics and Clinical Biology, 2024)
General Background: Chronic tonsillitis is a prevalent condition in children, often linked to various immunogenetic factors that influence its pathogenesis and associated diseases. Specific Background: The role of HLA (Human Leukocyte Antigen) system A and B loci in chronic tonsillitis remains inadequately understood, particularly regarding their clinical significance and the immunogenetic correlations with related conditions. Knowledge Gap: While prior studies have examined the genetic factors associated with chronic tonsillitis, there is a lack of comprehensive research focusing on the specific HLA loci and their implications for clinical outcomes in affected children. Aims: This study aims to determine the indicators of HLA A and B loci in children with chronic tonsillitis and to explore the clinical-immunogenetic correlations with associated diseases. Results: The findings demonstrate significant associations between specific HLA alleles and the severity of chronic tonsillitis, highlighting potential immunogenetic predispositions that influence disease progression and comorbidities. Novelty: This research introduces a novel perspective by linking HLA system indicators directly to clinical outcomes, thereby providing new insights into the immunogenetic mechanisms underlying chronic tonsillitis in children. Implications: The identification of these immunogenetic factors could enhance the understanding of chronic tonsillitis pathophysiology and inform personalized treatment strategies, ultimately improving patient management and outcomes in pediatric populations.